ANALYSIS STUDY OF THE BOOK AL-KASHFU WA-TABYIN IN SUFISM LEARNING TO DEVELOP RELIGIOSITY FROM THE PERSPECTIVE OF IMAM AL-GHAZALI - Fajar Akbar, Meiza; Sumanta; Khoirul Rozak, Anam; Ulfadhilah, Khairunnisa (International Journal of Multidisciplinary Reseach, 2025)
This research is titled "Analysis Study of the Book Al-Kashfu wa-Tabyin in Sufism Learning to Develop Religiosity from the Perspective of Imam Al-Ghazali". This research aims to analyze the role of the book Al-Kashfu wa-Tabyin in Sufism learning to develop students' religiosity, highlighting the perspective of Imam Al-Ghazali. The method used in this research is library research, which involves collecting and analyzing various relevant literature, particularly the book Al-Kashfu wa-Tabyin and the works of Imam Al-Ghazali related to the concept of religiosity in Sufism. The research findings indicate that the development of religiosity thru Sufism learning can be categorized into three main aspects: (a) Religious Belief, which is the strengthening of fundamental beliefs toward religious teachings and spiritual values; (b) Religious Commitment, which is a high commitment to consistently practicing religious teachings in daily life; and (c) Religious Behavior, which is real behavior that reflects religious values, such as honesty, empathy, and simplicity. The book Al-Kashfu wa-Tabyin, from the perspective of Imam Al-Ghazali, is an important source for instilling Sufistic values that focus on purifying the heart and strengthening spiritual connection with Allah SWT. Thus, learning Sufism based on this classical work can be an effective strategy for developing holistic religiosity that encompasses aspects of belief, commitment, and behavior. This study recommends integrating Sufism teachings and classical texts into the Islamic education curriculum to cultivate religious individuals with character.